2020
DOI: 10.3389/fpsyg.2020.617001
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Pregnant and Postpartum Women During the Coronavirus Disease 2019 Pandemic: A Systematic Review and Meta-Analysis

Abstract: Background: Prenatal and postnatal mental disorders can exert severe adverse influences on mothers, fetuses, and children. However, the effect of the coronavirus disease 2019 (COVID-19) pandemic on the mental health of pregnant and postpartum women remains unclear.Methods: Relevant studies that were published from January 1, 2019 to September 19, 2020 were identified through the systematic search of the PubMed, EMBASE, and Web of Science databases. Quality assessment of included studies, random-effects meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
225
6
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(263 citation statements)
references
References 65 publications
(213 reference statements)
16
225
6
16
Order By: Relevance
“…Yan et al, in a systematic analysis of 23 studies found that prevalence rates of anxiety, depression, psychological distress, and insomnia among pregnant women during the COVID-19 pandemic were more as compared with the pre-COVID era. In the same analysis, it was also found that multigravidae and women in the first and third trimesters of pregnancy were more vulnerable as compared with other pregnant women (17). In a survey conducted in Sri-Lanka, it was found that multigravidae were more susceptible to anxiety and depression as compared with primigravidae.…”
Section: Discussionmentioning
confidence: 89%
“…Yan et al, in a systematic analysis of 23 studies found that prevalence rates of anxiety, depression, psychological distress, and insomnia among pregnant women during the COVID-19 pandemic were more as compared with the pre-COVID era. In the same analysis, it was also found that multigravidae and women in the first and third trimesters of pregnancy were more vulnerable as compared with other pregnant women (17). In a survey conducted in Sri-Lanka, it was found that multigravidae were more susceptible to anxiety and depression as compared with primigravidae.…”
Section: Discussionmentioning
confidence: 89%
“…The psychological and social consequences of lockdown can be devastating for high-risk populations, such as pregnant women [14]. The prevalence rates of anxiety, depression, psychological distress, and insomnia among pregnant women during the COVID-19 pandemic have been documented to be as high as 37% (95% confidence interval (CI): 25-49%), 31% (95% CI: 20-42%), 70% (95% CI: 60-79%), and 49% (95% CI: 46-52%), respectively [15].…”
Section: Introductionmentioning
confidence: 99%
“…As per previous reports, women are much more vulnerable to stress (46) and showed significantly higher emotional distress than men in isolation during the threat of COVID-19 (47). Yan et al (48) launched a meta-analysis and revealed the prevalence rates of ANDP during the COVID-19 pandemic are significantly higher than those in the general population (48). Besides, a current longitudinal study across racial and ethnic groups of women during the prenatal and postpartum periods showed that depressive and anxiety symptoms were higher during COVID-19 relative to pre-COVID-19.…”
Section: Discussionmentioning
confidence: 54%